2021
DOI: 10.3389/fpsyg.2021.730972
|View full text |Cite
|
Sign up to set email alerts
|

From Self-Esteem to Selflessness: An Evidence (Gap) Map of Self-Related Processes as Mechanisms of Mindfulness-Based Interventions

Abstract: Self-related processes (SRPs) have been theorized as key mechanisms of mindfulness-based interventions (MBIs), but the evidence supporting these theories is currently unclear. This evidence map introduces a comprehensive framework for different types of SRPs, and how they are theorized to function as mechanisms of MBIs (target identification). The evidence map then assesses SRP target engagement by mindfulness training and the relationship between target engagement and outcomes (target validation). Discussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 168 publications
(242 reference statements)
0
18
0
Order By: Relevance
“…Notably, MBIs have been shown able to target transdiagnostic symptoms ( Compen & Speckens, 2021 ; Greeson, et al, 2018 ). Britton et al (2021) have reviewed specifically how self-related processes may be key mechanisms of MBIs, and found that MBIs consistently seem to reduce rumination, a transdiagnostic process with clear rigidity. They concluded however that the evidence supporting these theories is currently unclear, as few such processes have been measured in MBIs, and additional research using well-validated measures is needed.…”
Section: Mindfulness Meditation As Altering Self-patterns In Clinical...mentioning
confidence: 99%
“…Notably, MBIs have been shown able to target transdiagnostic symptoms ( Compen & Speckens, 2021 ; Greeson, et al, 2018 ). Britton et al (2021) have reviewed specifically how self-related processes may be key mechanisms of MBIs, and found that MBIs consistently seem to reduce rumination, a transdiagnostic process with clear rigidity. They concluded however that the evidence supporting these theories is currently unclear, as few such processes have been measured in MBIs, and additional research using well-validated measures is needed.…”
Section: Mindfulness Meditation As Altering Self-patterns In Clinical...mentioning
confidence: 99%
“…For instance, by drawing on evidence that certain MoAs are consistently not associated with behaviour change, theory authors could remove relevant constructs from their theories. The ontology can also be used to map evidence about MoAs onto its classes, as part of creating an "evidence-gap map" (Britton et al, 2021). Such maps can help researchers identify MoAs that require more study and avoid repeatedly investigating the same MoAs.…”
Section: Discussionmentioning
confidence: 99%
“…Depression can result from a complex interaction of psychological, physical, behavioral, and other factors (Pandey, 2021; Ratanasiripong, 2012; World Health Organization, 2017), and there are various treatment mechanisms (Britton, 2021; Xie, 2021). For example, pharmacotherapy mainly reduces the activity of brain nerves by reducing neurotransmitters in the body, thus stabilizing the mood of patients with depression; psychological therapy as well as educational program and training aim to correct cognitive bias, improve behavioral coping ability, and promote positive behaviors to empower the suffers of depression.…”
Section: Methodsmentioning
confidence: 99%
“…Depression can result from a complex interaction of psychological, physical, behavioral, and other factors (Pandey, 2021;Ratanasiripong, 2012;World Health Organization, 2017), and there are various treatment mechanisms (Britton, 2021;Xie, 2021).…”
Section: Conceptual Frameworkmentioning
confidence: 99%